CALHM5 deficiency alleviates aortic aneurysm by regulating smooth muscle calcium homeostasis - Bo Yang; Ting Xu; Qianqian Yang; Liangzhu Mo; Jianyi Huo; Taiyang Mu; Yating Zhi; Yun Du; Haojie Wang; Lingchuan Guo; Zhen Zhu; Yulong Feng; et al. (Proceedings of the National Academy of Sciences, 2026)
Ion channels are the second most common clinical drug target besides G protein–coupled receptors. Aneurysmal diseases pose a significant threat to human life. Novel drug targets for its treatment remain to be explored. We investigated the role of an ion channel, calcium homeostasis modulators 5 (CALHM5), on the development of aortic aneurysms. We characterized CALHM5 as a plasma membrane ion channel abundant in smooth muscle cells of both humans and mice, playing a pivotal role in regulating calcium homeostasis. Notably, CALHM5 deficiency suppressed the transcription of the L-type calcium channel (LTCC) pore-forming subunit by downregulating cAMP-response element binding proteins. This in turn diminished blood vessel contractility and decreased blood flow. Intriguingly, CALHM5 expression is downregulated in smooth muscle tissues of aortic aneurysm patients. Furthermore, CALHM5 deficiency was observed to ameliorate the development of abdominal aortic aneurysms in mice, partly by stimulating smooth muscle cell proliferation. CALHM5 emerges as an ion channel prominently expressed in arterial smooth muscles, serving as a physiological regulator of smooth muscle contraction and presenting itself as a promising therapeutic target for aortic aneurysms.